Atherogenic Index of Plasma in the Three Trimesters of Pregnancy - Hamadameen, Bana K.; Hamad, Sara S. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2023)
This study investigates the change that occurs for atherogenic index of plasma (AIP) which is a very good marker for the evaluation of the risk of atherogenicity and cardiometabolic health. This study indicates the logarithm of the triglyceride and high-density lipoprotein cholesterol (log [TG/HDL-c]). The parameters of triglycerides (TG) and high-density lipoprotein cholesterol (HDL-c) are estimated and compared with the control cases. The AIP is calculated for each case during pregnancy in first, second, and third trimesters separately and each is compared with control cases. The study population comprised (80) women aged between (20–40) years distributed to (20) healthy non-pregnant women, (20) in the first trimester, (20) in the second trimester, and (20) in the third trimester in Koya health centers. The results of this study showed a significant increase in the TG level in both the second and third trimesters of pregnancy compared to the control cases. Whereas, in the first trimester of pregnancy, it can be assumed that there is a non-significant decrease of TG level rather than control cases. As well as the serum levels of HDL for all three trimesters of pregnancy displayed non-significant changes when compared to non-pregnant cases. These data illustrate that the AIP levels during both the second and third trimesters of pregnancy are significantly higher, as compared to control cases, whereas the AIP levels in the first trimester are non-significantly elevated, as compared with control cases